VILDAGLIPTIN EFFICACY IN COMBINATION WITH METFORMIN FOR EARLY TREATMENT OF T2DM (VERIFY): BASELINE CHARACTERISTICS OFENROLLED PARTICIPANTS FROM MALAYSIA - FM, Zin; EM, Khoo; NA, Kamaruddin; DR, Matthews; PM, Paldnius; P, Proot; JE, Foley; M, Stumvoll; S, Del Prato (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Durable glycaemic control can delay diabetic complications and lead to improved quality of life in people with type 2 diabetes mellitus (T2DM). The ongoing VERIFY trial is the first study that aimed to determine the durability of glycaemic control with an early combination of vildagliptin and metformin versus metformin monotherapy in drugnaïve people with T2DM. Here we report the baseline characteristics of the subjects enrolled in the ongoing VERIFY study in Malaysia. METHODOLOGY VERIFY is a 5-year, recently concluded, multi-national, multi-ethnic, randomised, double-blind, two-arm, parallel-group study conducted across 34 countries in 254 centres. We randomised 28 participants from multi-ethnic population in Malaysia (global, n=2001), age ranged between 18–70 years, having glycated haemoglobin (HbA1c) levels between 48– 58 mmol/mol (6.5–7.5%) and body mass index (BMI) 22–40 kg/m2. Baseline measurements including HbA1c, fasting plasma glucose (FPG) and homeostasis model β-cell and insulin assessments were obtained at the screening visit, or at the next visit prior to initiation of metformin uptitration. RESULTS Among the patients randomized, there were 57.1% women; the median (±SD) disease duration was 1.1±3.22 months; mean (±SD) age was 49.9±10.04 years; weight 76.8±8.35 kg, and BMI 30.2±3.75 kg/m2. A total of 7.1% of participants were smokers. Baseline HbA1c was 6.9±0.2% and FPG was 6.6±0.81 mmol/L. The global HOMA-%β and% sensitivity values were 84% (60, 116) and 46% (31, 68), respectively. CONCLLUSION The population in this VERIFY study reflects the presence of insulin resistance with increased demand for insulin, and obesity. This study will provide information on opportunity for therapeutic intervention that focuses on durability of early glycaemic control.